The American Playwright, Edward Albee: Exploring the Powerful Dialogue of Edward Albee (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Edward Albee (1928- ) emerged with his extraordinaryone-Act plays in the late 1950's. Since then he has established himself to bethe most successful and critically acclaimed American dramatist commanding aglobal fame almost similar to that of his three illustrious senior playwrightsEugene O'Neill (1888-1953), Tennessee Williams (1911) and Arthur Miller (1915).Albee felt interested in experimenting with new dramatic forms as well as withExistentialistic themes. He has a good objective control over playwriting with afine ear for dialogue, reminding one of his equally illustrious Britishcounterparts the Absurdist playwright Harold Pinter (1930.), from the earlierplays, all the way to the powerful rhetoric of who’s Afraid of Virginia Woolf?(1982) or Tiny Alice (1964), Albee's chief characteristic is struck mostly inhis powerful dramatic dialogue.